2022
DOI: 10.1186/s12889-021-12383-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive determinants of overall survival among re-infected COVID-19 patients using the elastic-net regularized Cox proportional hazards model: a machine-learning algorithm

Abstract: Background Narrowing a large set of features to a smaller one can improve our understanding of the main risk factors for in-hospital mortality in patients with COVID-19. This study aimed to derive a parsimonious model for predicting overall survival (OS) among re-infected COVID-19 patients using machine-learning algorithms. Methods The retrospective data of 283 re-infected COVID-19 patients admitted to twenty-six medical centers (affiliated with Sh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Using the pre-selected features as predictors, we performed Elastic Net regularization. The process that we used has two tuning parameters: the regularization parameter lambda and the mixing parameter alpha for moderating between Lasso and Ridge [ 29 ]. The optimal model should specify alpha and lambda, for which the two repeated 5-fold cross-validated penalized log-likelihood deviance is minimal after comparing all the training datasets from 40 imputed datasets.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the pre-selected features as predictors, we performed Elastic Net regularization. The process that we used has two tuning parameters: the regularization parameter lambda and the mixing parameter alpha for moderating between Lasso and Ridge [ 29 ]. The optimal model should specify alpha and lambda, for which the two repeated 5-fold cross-validated penalized log-likelihood deviance is minimal after comparing all the training datasets from 40 imputed datasets.…”
Section: Methodsmentioning
confidence: 99%
“…The process that we used has two tuning parameters: the regularization parameter lambda and the mixing parameter alpha for moderating between Lasso and Ridge [29].…”
Section: Cox Models With Elastic Net Regularization (Coxen)mentioning
confidence: 99%
“…Zeng et al reported developing a machine-learning model to predict severe chronic obstructive pulmonary disease exacerbations: a retrospective cohort study ( 48 ). Ebrahimi et al reported predictive determinants of overall survival among re-infected patients with COVID-19 using the elastic-net regularized Cox proportional hazards model: a machine-learning algorithm ( 49 ). Together, these studies further supported the feasibility of machine-learning approaches to problem solving.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Ebrahimi et al 20 developed a ML model for predicting overall survival (OS) among reinfected COVID-19 patients. Two ML algorithms were applied – elastic-net regularised Cox-adjusted PH model and backward stepwise elimination – to a dataset of 283 reinfected COVID-19 patients admitted to 26 medical centres in Iran.…”
Section: Introductionmentioning
confidence: 99%